Improving Reading Ability Using Cooperative Integrated Reading and Composition (CIRC) Learning Method in Class XI Students of SMAN 1 Gunungsari - Saofa, Muhammad; Ramadahan, Iqbal; Adnan, Sofyan (Journal of Education and Social Science, 2025)
This study investigates the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning method in enhancing the reading ability of Class XI students at SMAN 1 Gunungsari. The research was conducted as a classroom action study, employing a cyclical process of planning, action, observation, and reflection. Data were collected through reading performance assessments, student questionnaires, and observational field notes. The findings reveal a significant improvement in students' reading comprehension, vocabulary acquisition, and critical analysis skills after implementing the CIRC method. Additionally, the collaborative nature of CIRC fostered greater student engagement and active participation in learning activities. The study concludes that the CIRC learning method is an effective pedagogical approach for improving reading skills in secondary education and recommends its broader application to enhance literacy outcomes. Further research is suggested to explore the method’s adaptability across diverse learning contexts and student demographics.